“Unless someone like you cares a whole awful lot, nothing is going to get better”: an environmental discourse analysis of animated films The Lorax (2012) and Tomorrow (2019) - M. Mizan-Rahman (Geoscience Communication, 2024)
Fostering understanding and support for environmental and climate issues requires a foundational understanding of how environmental discourse interacts with the public. Animated films exist as a medium in which environmental messaging is distributed to the public with the goal of inducing behavioral change in an audience. The goal of this paper is to link the messaging of such films with audience feedback. This will be accomplished by analyzing the impact of two environmentally focused animated films, The Lorax and Tomorrow, produced in Hollywood (United States) and Dhallywood (Bangladesh), respectively, and by using environmental humanities discourse analysis to examine how people responded to these films on social media websites. The first part of the article is the analysis of selected social media pages to understand the impact of these two films on contemporary environmental discourse, and the second part comprises an analysis of the environmental narrative of the films. I selected these two films for four reasons: (i) they are both environmental educational and pedagogical tools, (ii) they use environmental storytelling, (iii) they both address sustainability, and (iv) they may have influenced some discourse on environmental issues on social media. The study demonstrates that environmentally driven animated films can affect and shape the discourse of their audiences. This study also demonstrates how narratives from films such as The Lorax and Tomorrow can lead an audience to consider large-scale environmental issues.